1993
DOI: 10.1159/000310430
|View full text |Cite
|
Sign up to set email alerts
|

Frosted Retinal Periphlebitis in the Acquired Immunodeficiency Syndrome

Abstract: Six patients with the acquired immunodeficiency syndrome had frosted periphlebitis associated with large areas of cytomegalovirus retinitis. Following the administration of ganciclovir, periphlebitis resolved within 2–6 weeks concomitant with quieting of cytomegalovirus retinitis. Frosted retinal periphlebitis in the acquired immunodeficiency syndrome is associated with cytomegalovirus retinitis in North America. Medical treatment of cytomegalovirus retinitis leads to resolution of the periphlebitis without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The clinical manifestations of HIV-associated CMV retinitis include the classic features of necrotizing retinitis, with variable degrees of hemorrhaging ("cottage cheese with ketchup" or "pizza pie" retinopathy), as well as a granular form of retinitis that is sometimes in combination with frosted branch angiitis; associated inflammatory signs are lacking. [27][28][29][30][31] In contrast to clear media observed by Kuo et al, 6 all of our patients demonstrated associated vitritis, and more than half had concurrent anterior uveitis, while the absence of intraocular inflammation in patients with HIV infection and CMV retinitis is typical. [27][28][29][30][31] Our findings clearly show that the characteristics of posterior segment involvement caused by CMV in patients without HIV infection represent a much wider spectrum of clinical manifestations, which include frequent prevalence of retinal arteritis, variable signs of intraocular inflammation, and the presence of retinal involvement, varying from focal lesions to extended ARN.…”
Section: Commentmentioning
confidence: 66%
See 2 more Smart Citations
“…The clinical manifestations of HIV-associated CMV retinitis include the classic features of necrotizing retinitis, with variable degrees of hemorrhaging ("cottage cheese with ketchup" or "pizza pie" retinopathy), as well as a granular form of retinitis that is sometimes in combination with frosted branch angiitis; associated inflammatory signs are lacking. [27][28][29][30][31] In contrast to clear media observed by Kuo et al, 6 all of our patients demonstrated associated vitritis, and more than half had concurrent anterior uveitis, while the absence of intraocular inflammation in patients with HIV infection and CMV retinitis is typical. [27][28][29][30][31] Our findings clearly show that the characteristics of posterior segment involvement caused by CMV in patients without HIV infection represent a much wider spectrum of clinical manifestations, which include frequent prevalence of retinal arteritis, variable signs of intraocular inflammation, and the presence of retinal involvement, varying from focal lesions to extended ARN.…”
Section: Commentmentioning
confidence: 66%
“…6,26 Ocular manifestations of CMV infection in hosts with HIV infection have been extensively reported. 2,[26][27][28][29][30][31] However, systematic studies 5,6 on the clinical manifestations of CMV infection in posterior eye segments among patients without HIV infection are rare.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be primary FBA or secondary to ocular infectious diseases, such as CMV, syphilis, HSV, VZV, tuberculosis, toxoplasmosis, and non-infectious diseases, such as autoimmune diseases and haematological malignancies in the non-HIV-infected population [ 6 ]. Antigen-antibody complex deposition and direct CMV infection of the vessel wall are the underlying pathogeneses [ 7 , 8 ]. In the setting of HIV infection, FBA is an uncommon sign.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of HIV infection, FBA is an uncommon sign. Apart from the syphilis-related case [ 9 ], reported cases were exclusively associated with CMV retinitis [ 7 , 8 , 10 16 ] (summarised in Table 1 ). Currently, only two cases of FBA were associated with paradoxical IRIS [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%